An analysis of targeted single nucleotide polymorphisms for the risk prediction of gestational diabetes mellitus in a cohort of Malaysian patients - Nor Khatijah Mohd Aris,; Nor Azlin Mohamed Ismai,; Zaleha Abdul Mahdy,; Shuhaila Ahmad,; Norzilawati Mohd Naim,; Harlina Halizah Haji Siraj,; Rohana Jaafar,; Shareena Ishak,; Roslan Harun,; Rahman Jamal,; Wan Zurinah Wan Ngah,; Syed Zulkifli Syed Zakaria, (UKM Medical Molecular biology Institute, UMBI, 2011)
Recent association studies have described genetic variants among type 2 diabetes mellitus (T2DM) and their related traits. Gestational diabetes mellitus (GDM) is pathophysiologically similar to T2DM and may share genetic susceptibility.However, genetic susceptibility within GDM in our own population is still not yet explored. This study was to determine the association of GDM genetic variants in the Malaysian population.We genotyped 384 T2DM related SNPs among 174 cases of GDM and 114 controls of pregnant women using Illumina’s Golden Gate genotyping assay. In this case-control study, a custom of 384-SNP plex of 236 candidate genes was designed using the Illumina’s Assay Design Tool. The data analysis showed 12 SNPs had a significant association with GDM among Malaysians with p values 0.002 to 0.048 with their respective odd ratios. The SNPs rs7754840, rs10946398, rs9465871, rs7756992, rs6823091, rs7935082,rs237889, rs7903146, rs7961581 were significant under additive model while rs10811661, rs1016472, rs2270031 were associated with GDM under recessive model. Three SNPs namely rs7935082, rs1016472 and rs2270031 had reduced risk towards GDM while another nine SNPs which were rs7754840, rs10946398, rs9465871, rs7756992,rs10811661, rs6823091, rs237889, rs7903146 and rs7961581 had increased risk as much 1.75 to 2.62 times. Twelve genetic variants of T2DM were replicated in the SNP profiling among Malaysians GDM. Thus with a more significant result in a bigger sample, SNP screening is potentially a useful method in predicting the risk of gestational diabetes mellitus.